Entrapment ulnar neuropathy caused by cysticercosis - Ray, Munni; Kothur, Kavitha (Journal of Pediatric Neurology, 2006)
We report a 12-year-old child from North India with cysticercosis presenting as an ulnar entrapment neuropathy due to a compressive mass in the flexor digitorum profundus. Magnetic resonance imaging suggested an inflammatory mass compressing the neurovascular bundle. The histologic diagnosis was consistent with cysticercosis. Such solitary presentation of entrapment neuropathy with cysticercosis is extremely rare, and to our knowledge, this is the only case reported in pediatric literature.
Keywords: Ulnar nerve; entrapment neuropathy; cysticercosis